Decision-making among patients and their family in ALS care: a review. Issue 3 (3rd April 2018) - Foley, Geraldine; Hynes, Geralyn
Abstract: Objectives: Practice guidelines in ALS care emphasise the role of the patient and their family in the decision-making process. We aimed to examine the ALS patient/family relationship in the decision-making process and to ascertain how patients and their family can shape one another's decisions pertaining to care. Methods: We conducted a review of peer-reviewed empirical research, published in full and in English between January 2007 and January 2017, relating to care decision-making among ALS patients and their family. Database sources included: Medline; CINAHL; AMED; PsycINFO; PsycARTICLES; and Social Sciences Full Text. A narrative synthesis was undertaken. Results: Forty-seven studies from the empirical literature were extracted. The family viewpoint was captured primarily from family members with direct care-giving duties. Patients' cognitive status was not routinely assessed. The findings revealed that the decision-making process in ALS care can be contoured by patients' and family caregivers' perceived responsibilities to one another and to the wider family. Conclusions: Greater attention to family member roles beyond the primary caregiver role is needed. Strategies that integrate cognitively-impaired patients into the family decision-making process require investigation. Identification of the domains in which ALS patients and their family members support one another in the decision-making process could facilitate the development of patient/family decision-making tools in ALS care.